An Eye-Movement Analysis of Overt Visual Attention During Consecutive and Simultaneous Interpreting Modes in a Remotely Interpreted Investigative Interview - Doherty, Stephen; Martschuk, Natalie; Goodman-Delahunty, Jane; Hale, Sandra (Frontiers in Psychology, 2022)
Remote interpreting via video-link is increasingly being employed in investigative interviews chiefly due to its apparent increased accessibility and efficiency. However, risks of miscommunication have been shown to be magnified in remote interpreting and empirical research specifically on video-link remote interpreting is in its infancy which greatly limits the evidence base available to inform and direct evidence-based policy and best practice, particularly in the identification of the optimal mode(s) of interpreting to be used, namely consecutive and simultaneous. Consecutive interpreting refers to a process in which the interpreter transfers short segments of speech from one language into the other as each person speaks in managed turn-taking, while simultaneous interpreting refers to the transfer of natural speech from one language into another in a concurrent manner without the need for speakers to segment their speech. This study provides novel empirical evidence by using eye tracking to compare the overt visual attention of interpreters working in a remote setting in which an English-speaking Interviewer interacts with a non-English-speaking Suspect in person, for whom interpretation is provided via video-link in real time. Using a within-subject design, we analyse eye-movement data from 28 professionally accredited interpreters who interpreted via video-link an investigative interview in which consecutive and simultaneous interpreting modes were counterbalanced. Taking interpreting performance into account, our results showed that, the consecutive mode yielded significantly less gaze time and therefore significantly less on-screen overt visual attention due to off-screen notetaking, an essential component of the consecutive interpreting mode. Relative to gaze time, the consecutive mode also resulted in significantly more and longer fixations and shifts of attention. Participants also allocated significantly more overt visual attention to the Interviewer than the Suspect, particularly in the consecutive mode. Furthermore, we found informative significant correlations between eye tracking measures and interpreting performance: accuracy, verbal rapport, and management. Finally, we found no significant differences between the three language pairs tested. We conclude with a discussion of limitations and the contributions of the study and an outline for future work on this topic of growing importance.